In-Vitro Anti-Microbial and Anti-Urolithiatic Models for Extract of Parmelia Perlata Lichen: An Evaluation of Prophylactic Management against Kidney Stone (Global Journal of Medical Research, 2020)
Phyto-medicine is regaining interest owing to its advantages over conventional drugs and increasing cases of drug resistance. Moreover, recurrence and persistent side effects of present-day treatment for urolithiasis restrict their use, so an alternate solution using phytotherapy is being sought. The lichen species Parmelia Perlata (family Parmeliaceae) mentioned in India Materia Medica are useful in treating several ailments, and they are being used in large quantities as a food supplements in India.
Keywords: parmelia perlata; lichen; phytochemicals; antimicrobial; anti-urolithiatic